Pengaruh Kecerdasan Emosional dan Kemampuan Berpikir Positif Terhadap Kemampuan Berpikir Kritis Ilmu Pengetahuan Alam di SD Negeri 17 Tanjungpandan Belitung: Penelitian - Khairunnisa, Ejka Sabila; Bahij, Azmi Al; Hadi, Muhamad Sofian (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to analyze the influence of emotional intelligence and positive thinking on elementary students’ critical thinking skills in science learning. The research employed a survey method with a quantitative approach and path analysis, involving 652 students from Grades IV to VI at SD Negeri 17 Tanjungpandan Belitung. Data were collected through a science critical thinking test and validated questionnaires measuring emotional intelligence and positive thinking. The findings show that emotional intelligence has a direct and significant effect on students’ critical thinking skills, while positive thinking serves as a stronger predictor of critical thinking performance. Emotional intelligence also significantly influences positive thinking. In addition, an indirect effect of emotional intelligence on critical thinking was identified through positive thinking as a mediating variable. These results highlight that the development of students’ critical thinking skills requires not only cognitive ability but also emotional readiness and adaptive thinking patterns. Therefore, science learning should integrate strategies that strengthen emotional regulation and promote positive thinking.